Treatment Seeking Practices for Malaria: A Household Case of Uasin Gishu County, Kenya - Caroline, Kerich J.; William, Kemei K.; Cleophas, Cherop K. (European Scientific Journal, ESJ, 2018)
Introduction: Malaria is among the leading cause of morbidity and mortality in Kenya. Malaria treatment seeking practices in epidemic areas in Africa such as Kenya are not well studied. The study aimed at assessing the treatment seeking practices in residents of Uasin-Gishu County following Malaria infection. Methods: Study was cross sectional study design. Stratified random sampling was used to identify 341 study participants. Principal component analysis was applied to compute the wealth index and the chisquare tests of association were carried out to determine factors associated with choice of treatment. Multivariate logistic regression determined predictors of treatment seeking practices. P<0.05 significance level was used during the study. Results: Fever was reported in 62.8% of all households; 94% sought treatment for the fever. Commonly assessed facility was government health facility (63%), chemists (15%), private clinics (12%) and traditional healers (2%). Educated persons’ were 8.7 fold more likely to seek care from a private hospital. Employed and business owners were 4.1 fold more likely to purchase medicines from chemists. There were significant negative associations between wealth index and education level and seeking care in a government health facility. Respondents in the middle and fourth quintile with tertiary education level rarely sought care from a government health facility respectively. Conclusion: Treatment practices among households were: through government health institutions, private/clinics and chemists. Wealth index, age category of household heads, education level and occupation influenced treatment seeking practice. Reccomendation: There is need for the government for the government to strength community-based interventions and health facilities